Derechos humanos en tiempos de inseguridad ciudadana: experiencia canadiense a la luz del derecho interamericano - Provost, René (2017)
Canada’s experience in the war against terrorism goes back to the seventies, and continues to develop nowadays, with the last direct terrorist activity in 2017. The Canadian Government reacted to these terrorist attacks by enacting a number of statutes that reflect a changing international paradigm in relation to the fight against terrorism. Fundamental rights and liberties such as the freedom of expression, the right to private life and to personal freedom have been curtailed by these legislative measures. The practical consequences of these measures are analyzed via a comparative examination of the Inter-American System of Human Rights. In general terms, the war against terrorism produces significant impacts over the human rights.